Tingkat Pengetahuan Membaca Peta Buta pada Peserta Didik Sekolah Menengah Pertama - Ahmad Ramadhan Ikhsan; Putri Tipa Anasi; Hadi Wiyono; Diah Trismi Harjanti (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Research related to the level of knowledge of reading blind maps in students is important to determine the understanding of the location of the area as a form of basic Geography skills that are very much needed by students in 21st century learning. This study aims to determine the level of knowledge of reading blind maps and the basic elements of maps in Junior High School students. The knowledge indicators analyzed include three indicators, namely the indicator of remembering (C1), understanding (C2), and applying (C3). This study uses a descriptive quantitative method. Approximately 34 students were selected using a total sampling technique with data analysis using descriptive percentages and Guttman scale questionnaires. Based on the results of the study, the level of knowledge of students in the remembering indicator has a very high percentage, namely 93.3%; the indicator of understanding is 83.3%; and the indicator of applying is 70.5%, while the level of knowledge of map elements in students in the indicator of knowledge of blind maps is 76.8%, the indicator of function on the map is 62.8%, and the indicator of map elements is 86.2%. Therefore, it can be concluded that students have a level of knowledge and know the basic elements on the map with a very high classification.